Bright Light Therapy for Parkinson Disease: A Literature Review and Meta-Analysis of Randomized Controlled Trials - Hsu-Tung Huang (MDPI AG, 2021)
Sleep disorders and depression are significant nonmotor symptoms (NMSs) of Parkinson disease (PD). However, few effective, evidence-proven medical treatments are available for alleviating these symptoms. Bright light therapy (BLT) is a well-established treatment for circadian rhythm sleep disorders and seasonal affective disorder. The present study conducted a literature review for the effect of BLT on PD, especially a meta-analysis of randomized controlled trials (RCTs). We searched for studies using the PubMed and Cochrane Library databases. The major outcomes were the effects on sleep and depression. The effect on motor symptoms was also analyzed as a secondary outcome. This study was registered with PROSPERO (CRD42020204454). Six studies were included in the literature review only, and the other five RCTs were included in the meta-analysis. Despite the positive effects of BLT on PD patients, which were demonstrated in noncontrolled studies, in the meta-analysis of the RCTs, BLT did not significantly improve the depressive symptoms (standardized mean difference (SMD): −0.15, 95% confidence interval (CI): −0.48 to 0.17, p = 0.36) and excessive daytime sleepiness (EDS) (SMD: −0.12, 95% CI: −0.49 to 0.25, p = 0.53) in PD patients. Regarding motor symptoms, no significant beneficial effects were conferred (SMD: −0.11, 95% CI: −0.44 to 0.21, p = 0.49). In conclusion, BLT did not significantly alleviate depression and sleepiness. The inconsistency between BLT protocols, such as the varied timing, dosages, and treatment durations, may render BLT’s efficacy difficult to demonstrate. The small effect size obtained from the present meta-analysis indicates that future RCTs are necessary, for which BLT protocols are standardized and more patients are enrolled to determine whether a significant therapeutic benefit was conferred.